Graff's textbook of routine urinalysis and body fluids - Mundt, Lillian A.; Shanahan, Kristy (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins Health, 2011)
Graff's Textbook of Urinalysis and Body Fluids is the best urinalysis reference for laboratory students and professionals. In its Second Edition, this practical book retains its full-color images and top-notch coverage of urinalysis principles while significantly updating the content, broadening the scope to include new material on body fluids, providing more information on safety and quality assurance, and adding textbook features such as objectives, case studies, and study questions
Urinalysis clinical laboratory operations -- Renal anatomy and physiology and urine formation -- Collection and physical examination of urine -- Chemical analysis of urine -- Microscopic examination of urinary sediment -- Atlas of urinary sediment -- Urinary and metabolic diseases and related urinalysis findings -- Introduction to body fluids -- Cerebrospinal fluid analysis -- Serous body fluids -- Synovial fluid -- Semen analysis -- Fecal analysis -- Miscellaneous and body fluids -- Automation of urinalysis and body fluids examination
Rev. ed. of: A handbook of routine urinalysis / Laurine Graff. c1983
Includes bibliographical references and index
13
Keywords: Urine -- Chemistry; Urine -- Examination -- Handbooks